Association of 21-gene recurrence score assay and adjuvant chemotherapy use in the medicare population, 2008–2011. Issue 1 (January 2016) - Su, Kevin W.; Hall, Jane; Soulos, Pamela R.; Abu-Khalaf, Maysa M.; Evans, Suzanne B.; Mougalian, Sarah S.; Rutter, Charles E.; Davidoff, Amy J.; Gross, Cary P.
Abstract: Objectives: The 21-gene recurrence score (RS) assay helps guide adjuvant chemotherapy use for patients with breast cancer, and is predicted to reduce overall chemotherapy use. Little is known about recent patterns of testing in the Medicare program and the impact of testing on chemotherapy use as a function of patient age. Materials and Methods: We conducted a national claims—based study of Medicare beneficiaries age ≥ 66 years. We assessed trends in assay use (using multivariable regression), adjuvant chemotherapy use, and associated expenditures, for all patients and for two age strata: age 66–74 years and 75–94 years. Geographic variations in assay adoption and regional-level correlation between assay and chemotherapy use were measured. Results: We identified 132, 222 women who underwent breast surgery from 2008–2011. Assay use increased from 9.0% to 17.2% from 2008–2011 (p < .001), but chemotherapy use remained stable at 12.5% (p = .49). In younger patients, assay use increased from 14.3% to 23.7% (p < .001), while chemotherapy use decreased from 18.2% to 16.2% (p < .001). In older patients, assay use increased from 4.1% to 9.9% (p < .001), while chemotherapy use remained stable at 6.8% (p = .67). Mean per-beneficiary expenditures for testing and chemotherapy increased from $2030 to $2430 (p < .001). Regions with increased assay adoption were not more likely to reduce chemotherapy. Conclusion: Despite increased RS testing for both younger and older Medicare patients, there has only been a modest decrease in chemotherapy use for younger patients and no change for older patients, resulting in an overall increase in costs associated with gene expression profiling.